DESIGNING AN ON-GRID SOLAR POWER PLANT AT THE WOMEN'S DORMITORY BUILDING OF AVIATION POLYTECHNIC JAYAPURA - Bernandos, Markus; Perangin Angin, Andi Frianto; Pratama, Faridh Surya (Department of Mechanical Engineering Education, 2023)
Despite the abundance of solar energy potential in Indonesia, the utilization has not been optimal. PLN, as the state power grid provider, can not meet the increasing electricity demand in all regions of Indonesia. This research will discuss utilizing the potential of the On-Grid system PLTS planning on the Rooftop of the Jayapura Aviation Polytechnic Women's Dormitory Building in Tanjung Ria District, North Jayapura City. This PLTS design uses PvSyst programming to measure and analyze data from a complete solar PV system, aided by SketchUp Pro, to demonstrate 3D plan views. The result is data on the potential annual production of electrical energy, including the total energy produced, the energy distributed, and the value of the PLTS work ratio with data output. The configuration installed at the Poltekbang Jayapura women's dormitory is an AC Coupling On-Grid PLTS with 400 Wp Photovoltaic modules. From the PvSyst simulation that has been carried out, it can be obtained that the potential for electrical energy in the Jayapura Aviation Polytechnic Dormitory Building is 323,905 kWh / year with a PLTS capacity of 230 kWp with a Performance Ratio of 0,829.